IMPLEMENTASI PROGRAM SHALAT DHUHA DAN SHALAT ZUHUR BERJAMAAH DALAM PEMBENTUKAN AKHLAK SISWA (STUDI PADA SEKOLAH SD AL HIRA PERMATA NADIAH MEDAN) - Ra Jab (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine the implementation of the Dhuha prayer andZuhr prayer in congregation in the formation of student morals, and theimpact they cause and the supporting and inhibiting factors in theformation of student morals in the Al Hira Permata Nadiah School inMedan. This type of research is field research with a qualitativedescriptive approach. In this study, data collection techniques were carried out by observation, interviews, and documentation. The technique of checking the validity of the data uses the source triangulationtechnique. Analysis of the data used is an Interactive analysis model. Thesubjects of this study were students at Al Hira Permata Nadiah Medan.The results showed that through the habituation program Dhuha prayerand Zuhr prayer in congregation students were quite able to apply theirgratitude for all the blessings of Allah SWT both through words anddeeds. courtesy politeness towards everyone, especially parents andteachers, both in the form of words and deeds. Students can controlemotions or anger, but the mind and heart also become calmer, so that itwill facilitate the learning process.